A Preliminary Report on Brain-Derived Extracellular Vesicle as Novel Blood Biomarkers for Sport-Related Concussions - Kawata, Keisuke; Mitsuhashi, Masato; Aldret, Randy (Frontiers in Neurology, 2018)
The purpose of the study was to test the utility of unique panel of blood biomarkers as a means to reflect one's recovery process after sport-related neurotrauma. We established a panel of biomarkers that are reacted positive with CD81 (extracellular vesicle marker) and various neuron and glia specific antigens (e.g., neurofilament light polypeptide "NF-L", tau, synaptosome associated protein 25 "SNAP25", glial fibrillary acidic protein, myelin basic protein). We first evaluated test-retest reliabilities of brain-derived exosome markers, followed by an application of these markers in 8 professional ice-hockey players to detect cumulative neuronal burden from a single ice-hockey season. During the season, two players were diagnosed with concussions by team physician based on an exhibition of symptoms as well as abnormality in balance and ocular-motor testing. One player reached symptom-free status 7 days after the concussion, while the other player required 36 days for symptoms to completely resolve. Blood samples and clinical assessments including balance error scoring system and near point of convergence throughout recovery process were obtained. Biomarkers indicative of axonal damage, neuronal inflammation, and glial activation showed excellent test-retest reliabilities (ICC: 0.713 - 0.998, p's < 0.01). There was a statistically significant increase in the NF-L marker at post-season follow-up compared to pre-season baseline (Z = -2.100, P = 0.036), however the statistical significance did not withstand Bonferroni correction for multiple comparisons. In concussion cases, neuronal and microglia markers notably increased after concussions, with the unique expression patterns being similar to that of concussion recovery process. These longitudinal data coupled with excellent test-retest reliabilities of novel array of blood biomarkers potentially reflect the damage in neural cell structures and metabolic crisis due to concussion. However, future studies with larger sample size and appropriate control groups to evaluate sensitivity and specificity of these markers. This preliminary case report suggests the potential utility of multimodal blood biomarkers for concussion prognosis and recovery assessment.